Responses to Informal Accommodation Requests from Employees with Disabilites: Multistudy Evidence on Willingness to Comply - Florey, Anna T.; Harrison, David A. (Academy of Management Journal, 2000)
The authors developed and tested hypotheses describing the psychological process invoked when managers receive requests for accommodations from employees with disabilities. In two scenario-based experiments, obligation and attitude had consistent effects on managers' intentions to comply, mediating the influence of performance instrumentality and perceived fairness. Psychological reactions were affected by the controllability of a disability's onset, the employee's past performance, and the size of the requested accommodation.